PERSEPSI ORANG TUA TERHADAP PENDIDIKAN INKLUSIF SEKOLAH DASAR DI PROVINSI LAMPUNG - Hendrowati, Tri Yuni (STKIP Muhammadiyah Pringsewu, 2017)
This study aims to know parents perception toward the implemetation of inclusive education of elementary school in Lampung. This study used survey method. 411.005 parents who speread into 5900 elementary school in 2016 were taken apart as population of the research. The research sample were 399 parents in eight regency/ city in Lampung. In collecting the data, the researcher employed open- ended questionnaire. The data were analysed using percentage formula. The research finding shows that 74% parents agree to the application of inclusive education in elementary school, whereas 26% parents disagree with performance of inclusive education in elementary school. The most reason agree on the implementation of inclusive education states that every child has the same rights, while the most reason that disagree with the implementation due to fear of negative impact when their children mixed with special needs children.